Gamification in Efl Class using Quizizz as an Assessment Tool - Fuad Arifudin Abi Maryo; Endang Pujiastuti (Proceedings Series on Physical & Formal Sciences, 2022)
The teaching and learning process today is no longer carried out traditionally using books only, but many technologies are used to obtain a better teaching and learning process. The application of information, communication, and technology (ICT) tools in the field of education is increasingly widespread. This article discusses about the use of Quizezz as one of the learning media which can be used as an assessment tool. It has particular characteristics and advantages which can help students in reducing the anxiety in doing the exam or text. Therefore, the use of gamification, particularly Quizizz, can beused as the assessment tool during the classroom activity.